2022
DOI: 10.1136/bmjopen-2021-052725
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes and hypertension in Vietnam: a systematic review and meta-analysis of studies between 2000 and 2020

Abstract: ObjectivesThe objective of this study was to determine the level of type 2 diabetes (T2DM) and hypertension (HTN) in Vietnam and to assess the trend and recommend the future direction of prevention research efforts.DesignWe searched scientific literature, databases including PubMed, EMBASE, CINHAL and Google Scholar; grey literature and reference lists for primary research published, nation database websites between 1 January 2000 and 30 September 2020. We adapted the modified Newcastle Ottawa Scale for assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…We suppose that the prevalence of DM may have increased as a result of nutritional transition and urbanization. Thus, the difference in the prevalence of DM between our study and the earlier studies may be attributable to the passage of time, as some authors have indicated that the prevalence of DM can double in a country within a decade [ 14 ]. Our findings are in agreement with the rising trend in global diabetes prevalence.…”
Section: Discussionmentioning
confidence: 51%
“…We suppose that the prevalence of DM may have increased as a result of nutritional transition and urbanization. Thus, the difference in the prevalence of DM between our study and the earlier studies may be attributable to the passage of time, as some authors have indicated that the prevalence of DM can double in a country within a decade [ 14 ]. Our findings are in agreement with the rising trend in global diabetes prevalence.…”
Section: Discussionmentioning
confidence: 51%
“…The patients’ smoking status, hyperlipidemia, and lifestyle were not documented in our study. We found that the prevalence of diabetes and hypertension in our study participants was comparable to those of the adult Vietnamese population [ 32 ]. However, we found no association between CEs and these single underlying diseases as well as other common cardiovascular risk factors including previous MI or stroke and heart failure.…”
Section: Discussionmentioning
confidence: 69%
“…With a prevalence of 6.0%, diabetes is one of the most common non-communicable diseases in Vietnam. [ 22 ] According to multinational data, the prevalence of diabetes in patients with AF is 22.2%, and this proportion ranges from 15.7% to 44.4% in Vietnam. [ 5 – 7 ] Diabetes is a well-established risk factor for AF through multiple pathomechanisms.…”
Section: Patients With Diabetesmentioning
confidence: 99%